2021
DOI: 10.3390/ijms22115458
|View full text |Cite
|
Sign up to set email alerts
|

Loss of PKGIβ/IRAG1 Signaling Causes Anemia-Associated Splenomegaly

Abstract: Inositol 1,4,5triphosphate receptorassociated cGMP kinase substrate 1 (IRAG1) is a substrate protein of the NO/cGMP-signaling pathway and forms a ternary complex with the cGMPdependent protein kinase Iβ (PKGIβ) and the inositol triphosphate receptor I (IP3RI). Functional studies about IRAG1 exhibited that IRAG1 is specifically phosphorylated by the PKGIβ, regulating cGMPmediated IP3dependent Ca2+release. IRAG1 is widely distributed in murine tissues, e.g., in large amounts in smooth muscle-containing tissues a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…This was likely the cause of severe anemia in the patient 3 years prior to the study, or anemia was the cause of splenomegaly. [ 15 ] It was also considered that the abnormally proliferating accessory spleen compressed the branches of the splenic vein, which could have caused the dilation and rupture of veins in the gastric fundus. After the accessory spleen enlarged further, its demand for blood supply increased, and, at the same time, the blood vessels entering and leaving the accessory spleen became enlarged.…”
Section: Discussionmentioning
confidence: 99%
“…This was likely the cause of severe anemia in the patient 3 years prior to the study, or anemia was the cause of splenomegaly. [ 15 ] It was also considered that the abnormally proliferating accessory spleen compressed the branches of the splenic vein, which could have caused the dilation and rupture of veins in the gastric fundus. After the accessory spleen enlarged further, its demand for blood supply increased, and, at the same time, the blood vessels entering and leaving the accessory spleen became enlarged.…”
Section: Discussionmentioning
confidence: 99%
“…This translocation could not be observed in vascular smooth muscle cells (VSMCs) of global Irag1 -deficient mice [ 4 ]. However, the loss of the interaction between IRAG1 and PKGIβ may be the reason why protein expression of PKGIβ is reduced in Irag1 mouse mutants [ 3 , 4 , 16 , 17 ]. In contrast, the coiled-coil domain of IRAG1 is not involved in any interaction between IRAG1 and PKGIβ, but is necessary for the interaction of IRAG1 with the IP 3 R-I [ 1 ].…”
Section: Functional Features Of Irag1mentioning
confidence: 99%
“…These pathological changes could also be observed in global Irag1 -/- mice [ 4 ]. Further studies with these transgenic mice revealed that they had iron deficiency anemia as a result of gastrointestinal bleeding and subsequently developed splenomegaly [ 16 ]. The results verified indications of splenomegaly in earlier studies of Irag1 mouse mutants [ 3 , 4 ].…”
Section: Functional Features Of Irag1mentioning
confidence: 99%
See 1 more Smart Citation
“…This is accompanied by downregulation of the specific β-isoform of PKGI (PKGIβ) protein. This leads to the hypothesis, that a loss of PKGIβ/IRAG1 signaling causes these physiological defects [ 8 ].…”
Section: Communicationmentioning
confidence: 99%